2020
DOI: 10.1016/j.psj.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Stocking density effects on production qualities of broilers raised without the use of antibiotics

Abstract: In no antibiotics ever ( NAE ) broilers, enteric diseases pose a threat to intestinal health and generally welfare, which can be exacerbated because of stocking density. Through knowledge of litter condition and management, disease can be minimized, and broiler welfare can be improved. To evaluate how stocking density influences NAE broilers raised in conventional housing, we evaluated production traits for broilers raised at two stocking densities within a single commercial house. Over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…Litter quality is correlated with moisture levels and is impacted by the number of broilers in a flock [ 212 ]; therefore, litter amendments, changing litter, or windrowing may be included in NAE production to reduce microbial load. A recent study suggests stocking density influences litter moisture [ 213 ]. While commercial NAE settings revealed no significant difference in feed conversion, mortality, or body weight gain, a low stocking density (0.27 m 2 ) showed a 2.5% reduction in litter moisture when compared to the higher stocking density (0.23 m 2 ) [ 213 ].…”
Section: Disease Prevention Strategies In Naementioning
confidence: 99%
See 3 more Smart Citations
“…Litter quality is correlated with moisture levels and is impacted by the number of broilers in a flock [ 212 ]; therefore, litter amendments, changing litter, or windrowing may be included in NAE production to reduce microbial load. A recent study suggests stocking density influences litter moisture [ 213 ]. While commercial NAE settings revealed no significant difference in feed conversion, mortality, or body weight gain, a low stocking density (0.27 m 2 ) showed a 2.5% reduction in litter moisture when compared to the higher stocking density (0.23 m 2 ) [ 213 ].…”
Section: Disease Prevention Strategies In Naementioning
confidence: 99%
“…A recent study suggests stocking density influences litter moisture [ 213 ]. While commercial NAE settings revealed no significant difference in feed conversion, mortality, or body weight gain, a low stocking density (0.27 m 2 ) showed a 2.5% reduction in litter moisture when compared to the higher stocking density (0.23 m 2 ) [ 213 ]. Litter moisture has been associated with increased ammonia levels, increased bacterial load, and increased lesions such as footpad dermatitis, breast blisters, and hock burns [ 70 , 71 , 72 ].…”
Section: Disease Prevention Strategies In Naementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that HSD decreases the feed intake of broilers (Wang et al, 2014;Madilindi et al, 2018;Cengiz et al, 2018;Sanchez-Casanova et al, 2019;Magnuson et al, 2020;McKeith et al, 2020); however, scanty literature was reported about the mechanism of this action. Hypothalamus plays a critical role in the appetite regulation (Harrold et al, 2012;Everaert et al, 2019).…”
mentioning
confidence: 98%